Pembelajaran Pendidikan Agama Islam Masa Pandemi Covid 19 di SDN Leuwiranji 05 - Windy Dian Sari; Finki Alfitri Yeni; Siti Aliyah Fajrianah; Siti Nurfaidah (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
Education is the most important part, learning itself is an activity carried out by students to obtain change, Islamic religious education learns the moral and basic values related to worship, and with humans, Indonesia is faced with a pandemic so that learning activities are carried out on a distance system (PJJ). This research method uses qualitative research, and this type of research uses two types of primary data sources and skunder. Educators must be able to motivate students in the learning process, Islamic religious education is an effort to increase the power of faith and piety to Allah SWT, the spread of the virus (Covid-19) reported by the minister of education, emphasizing that the learning process is carried out using online media. E-Learning is a new thing, the covid-19 pandemic increasingly confirms the need for information technology as a solution to continue teaching and learning activities (KBM). This is where the important role of PAI teachers in shaping the character and morals of learners, of course, the right strategy is needed so that the role can be realized.